Media Card Quartet Dikda Art Dance Based on Outdoor Learning - Ariyanti, Siti Eva; Ary, Deasylina da (Universitas Negeri Semarang, 2020)
In dance education, in the second grade of Bawu 03 elementary school had not used innovative learning media, so that media development was needed in learning. This research aimed to develop, to find out the results of feasibility, and test the effectiveness of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material. The type of this study was Research and Development (R & D) adapted from Sugiyono's theory. The participants of this study were the second grade at Bawu 03 elementary school in the number of 41 students. Data analysis techniques included product data analysis, initial data analysis, and final data analysis in the form of t-test and n-gain test. The results showed that learning media in the media of DIKDA quartet cards on dance education based on outdoor learning was very feasible to use by obtaining a percentage of 96.88% by media experts, 96.88% by material experts and 93.75% by language experts. The results of small scale got a percentage of 100% of students and 92% of teachers and on a large scale get a percentage of 97,9% of students and 100% of teachers. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade. 88% by material experts and 93.75% by language experts. The results of small scale got a percentage of 100% of students and 92% of teachers and on a large scale get a percentage of 97,9% of students and 100% of teachers. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade. 88% by material experts and 93.75% by language experts. The results of small scale got a percentage of 100% of students and 92% of teachers and on a large scale get a percentage of 97,9% of students and 100% of teachers. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade.